A simple test for asymptotic stability in some dynamical systems - Ibargüen-Mondragón, Eduardo; Cerón Gómez, Miller; Romero Leitón, Jhoana Patricia (Revista de Ciencias, 2014)
A simple test for asymptotic stability in some dynamical systems